Three-dimensional brain arteriovenous malformation models for clinical use and resident training - Dong, Mengqi; Chen, Guangzhong; Li, Jianyi; Qin, Kun; Ding, Xiaowen; Peng, Chao; Zhou, Dong; Lin, Xiaofeng (Medicine (Baltimore), 2018)
To fabricate three-dimensional (3D) models of brain arteriovenous malformation (bAVM) and report our experience with customized 3D printed models of patients with bAVM as an educational and clinical tool for patients, doctors, and surgical residents. Using computerized tomography angiography (CTA) or digital subtraction angiography (DSA) images, the rapid prototyping process was completed with specialized software and "in-house" 3D printing service. Intraoperative validation of model fidelity was performed by comparing to DSA images of the same patient during the endovascular treatment process. 3D bAVM models were used for preoperative patient education and consultation, surgical planning, and resident training. 3D printed bAVM models were successful made. By neurosurgeons' evaluation, the printed models precisely replicated the actual bAVM structure of the same patients (n = 7, 97% concordance, range 95%-99% with average of < 2 mm variation). The use of 3D models was associated shorter time for preoperative patient education and consultation, higher acceptable of the procedure for patients and relatives, shorter time between obtaining intraoperative DSA data and the start of endovascular treatment. Thirty surgical residents from residency programs tested the bAVM models and provided feedback on their resemblance to real bAVM structures and the usefulness of printed solid model as an educational tool. Patient-specific 3D printed models of bAVM can be constructed with high fidelity. 3D printed bAVM models were proven to be helpful in preoperative patient consultation, surgical planning, and resident training.